Long Term Participant Athlete Development (LTPAD) (Speedskating Canada, 2018)
Plan des kanadischen Eisschnelllaufverbands zum lebenslangen Sporttreiben und zur Athletenentwicklung im Eisschnelllauf. das Modell umfasst 9 Stufen: Stage 1: Active Start (0-6 years) •Stage 2: FUNdamentals (girls 6-8, boys 6-9) •Stage 3: Learning to Train (girls 8-11, boys 9-12) •Stage 4: Training to Train (girls 11-15, boys 12-16) •Stage 5: Learning to Compete (females 15-17, males 16-18) •Stage 6: Training to Compete (females 17-21, males 18-21) •Stage 7: Learning to Win (ST males & females 21-23+, LT males & females 25+) •Stage 8: Training to Win (ST males & females 23+, LT males & females 25+) •Stage 9: Active for Life (any age participant, includes coaches, officials & volunteers)